HADIS DAN KESEHATAN MENTAL: PERSPEKTIF INTEGRATIF ANTARA TRADISI NABAWI DAN PSIKOTERAPI KONTEMPORER - Abdelsalam Ibrahim Issa Al-Mashay; Rabeeah Farj Amhimmid; Randi Purnama; Inong Satriadi (Journal International Inspire Education Technology, 2025)
The increasing prevalence of mental health problems in contemporary society has prompted scholars to explore integrative approaches that bridge psychology and religious traditions. This study aims to analyze the concept of mental health embedded in selected Hadith and to examine its relevance and convergence with contemporary psychotherapeutic approaches. The research method used by the researchers in this study is a qualitative, literature-based study, utilizing thematic and integrative analysis of authoritative Hadith compilations along with recent scholarly works in psychology and psychotherapy published in the last decade. The results of this study indicate that the Hadith offers a comprehensive framework for understanding mental well-being that emphasizes psychological balance and spiritual depth. This integrative perspective contributes to contemporary scholarship by demonstrating that the prophetic tradition can serve not only as a moral guide but also as a complementary resource for culturally and spiritually sensitive mental health interventions. The conclusions of this study emphasize the importance of interdisciplinary dialogue between Islamic studies and mental health sciences and highlight the potential of integrative models to enhance the effectiveness of therapy, especially in religiously oriented communities.